2004
DOI: 10.1158/1078-0432.ccr-03-0368
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Thyrotropin-Releasing Hormone by Human Melanoma and Nevi

Abstract: Purpose: Thyrotropin-releasing hormone (TRH) is a tripeptide hormone produced by the hypothalamus in response to hypothyroidism. RNA transcripts for the TRH prohormone have recently been described in melanoma cell lines. To expand these findings, we have examined cultured melanoma cells and melanocytes, human melanoma tumors, and nevi for the expression of TRH.Experimental Design: Five melanoma cell lines were analyzed by reverse transcription-PCR/Southern blotting for preproTRH message. The same melanoma line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 15 publications
(15 reference statements)
0
19
0
1
Order By: Relevance
“…The endocrine features of melanoma have been an active topic of research in our laboratory over the past several years. We have reported that melanoma cells produce thyrotropin releasing hormone (TRH) and respond to this peptide hormone by proliferation, suggesting the presence of an autocrine loop (1). We have also demonstrated the expression of functional thyroid stimulating hormone (TSH) receptors by human melanoma cells, which exhibit a proliferative response to TSH through activation of the mitogen-activated protein kinase (MAPK) pathway (2).…”
Section: Introductionmentioning
confidence: 99%
“…The endocrine features of melanoma have been an active topic of research in our laboratory over the past several years. We have reported that melanoma cells produce thyrotropin releasing hormone (TRH) and respond to this peptide hormone by proliferation, suggesting the presence of an autocrine loop (1). We have also demonstrated the expression of functional thyroid stimulating hormone (TSH) receptors by human melanoma cells, which exhibit a proliferative response to TSH through activation of the mitogen-activated protein kinase (MAPK) pathway (2).…”
Section: Introductionmentioning
confidence: 99%
“…TRH immunoreactivity (IR) has also been described in melanoma cells and in primary melanocyte cultures. Moreover, melanoma cells, but not normal melanocytes, respond to TRH stimulation in vitro with increased proliferation (18). Furthermore, it is also known that large amounts of TRH are produced in amphibian skin (19) in the epithelium lining the cutaneous glands in the epidermis (20).…”
mentioning
confidence: 99%
“…Some studies have reported that TSH is more likely to be expressed by dysplastic nevi than by benign nevi, and the dysplastic nevi of melanoma patients have a higher TSH expression than that of healthy individuals. Thus, TSH has been implicated in the malignant transformation of melanocytes to melanoma, and TSH stimulates the growth of melanoma cells 5,6 . On the other hand, the possibility has been suggested that the melanoma induces the thyroid dysfunction and this leads to hypothyroidism under the condition of low circulating thyroid hormone levels and concomitantly elevated TSH levels, although an autoimmune mechanism has also been suggested 2 .…”
Section: Discussionmentioning
confidence: 99%